Barack Obama's America How New Conceptions of Race, Family, and Religion Ended the Reagan Era - White, John Kenneth (Contemporary Political and Social Issues, 2009)
The election of Barack Obama to the presidency marked a conclusive end to the Reagan era, writes John Kenneth White in Barack Obama's America. Reagan symbolized a 1950s and 1960s America, largely white and suburban, with married couples and kids at home, who attended church more often than not.Obama's election marked a new era, the author writes. Whites will be a minority by 2042. Marriage is at an all-time low. Cohabitation has increased from a half-million couples in 1960 to more than 5 million in 2000 to even more this year. Gay marriages and civil unions are redefining what it means to be a family. And organized religions are suffering, even as Americans continue to think of themselves as a religious people. Obama's inauguration was a defining moment in the political destiny of this country, based largely on demographic shifts, as described in Barack Obama's America.